On the Alevism of Elbistan, Nurhak, Ekinozu and Afsin - Aksüt, Ali (Journal of Alevism-Bektashism Studies, 2017)
This paper includes the data and findings acquired through the field researches carried out on the locations of Elbistan, Nurhak, Ekinozu and Afsin, towns of Kahramanmaras province, where Alevi “dede” and aspirant communities live. It is given information about communities such as Dumbelu, Can Beglu, Karan, Kasan, Tab, Halac, Lek, Goran, Teberi, Ehl-i hak, Sebek and Kakai with the purpose of clarifying the historical roots of Alevi communities in the region, and the connections of these communities to the Alevi “ocaks” in the region are appraised through the information collected from available literature and oral sources. Also, the paper put emphasis on the relations between the Alevi “ocaks” in the region and historical persons such as Dede Garkın, Haci Bektas Veli, Kadincik Ana and Timur. Besides, a large part of the paper is dealing with the Sinemilli “ocak”, the most well-known of Alevi “ocaks” in the region. The paper includes new and original compilations and findings from available literature, archival documents and field researches about historical roots of the Sinemilli tribe and the Kantarma “ocak”, its structure and tribes, nomad groups and settlements related to this “ocak”.
Keywords: Alevis of Kahramanmaras; Alevis; Sinemilli “ocak”; Kantarma “ocak”; Elbistan; Nurhak; Ekinozu; Afsin